Human Immunodeficiency Virus Infection and Hodgkin's Lymphoma in South Africa: An Emerging Problem. (30th December 2010) - Patel, Moosa; Philip, Vinitha; Fazel, Fatima
Abstract : Hodgkin's lymphoma (HL) occurs with increasing frequency in human-immunodeficiency-virus-(HIV-) infected individuals. The natural history and behaviour of HIV-HL is different, being more atypical and aggressive. The association between HIV and HL appears to be primarily EBV driven. HAART use does not significantly impact on the incidence of HL. Indeed, the risk of HL has increased in the post-HAART era. However, the advent of HAART has brought renewed hope, allowing standard therapeutic options to be used more optimally, with better treatment outcomes. Despite the renewed optimism, the overall survival of HIV-HL patients remains less favourable than that in HIV-seronegative patients. This is particularly true in sub-Saharan Africa, where there is a significant burden of HIV/AIDS and where more than half the patients are HAART naive at diagnosis of HL. The similarities and differences of a South African cohort of HIV-HL are presented in this paper.